(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
The present paper reviews and improves the stratigraphy of the Cenozoic subsurface succession of the Venetian-Friulian Basin by means of a foraminiferal study, integrated by calcareous nannofossil analysis in some key stratigraphic intervals, of thirteen ENI wells drilled in the 60-70s and kept reserved since now.The Venetian Friulian Basin is a complex basin due to the superimposition of three overlapping foreland systems, during the Paleocene to Pleistocene time interval. These systems are related to the evolution of three collisional belts (Southern Alps, Apennines and Dinarides) which experienced structuring phases at different time intervals, with different belt orientation, vergence and topography. The peculiar location of the basin at the tectonic knot, between the Po Plain Basin and the Adriatic Basin that are the most important Italian sites of gas reservoirs, makes it as an interesting case-study both from a scientific and industrial point of view. Data of both foraminiferal and nannofossil assemblages were performed using, tentatively, the standard zonations proposed for the tropical-subtropical realm and the Mediterranean region. In the chronostratigraphic intervals where standard events were not recorded, other biohorizons from “regional” zonal schemes were applied. The data obtained allowed to check the applicability of the biohorizons used in the stated schemes to a subsurface succession analysed mainly from cuttings. Results allowed also to provide a rather precise biostratigraphic correlation of the thirteen studied wells which is a fundamental step to better describe the geometry of the sedimentary infill and to reconstruct the synoptic chronostratigraphic frame providing the timing of the sedimentary events and the main sedimentary or erosional hiatuses. Based on this chronostratigraphic scheme, the Cenozoic subsurface succession of the Venetian –Friulian Basin is subdivided into five depositional sequences (S1-S5) bounded by four major unconformities (U1-U4) and by their correlative conformity surfaces, regionally recognised throughout the basin.